Extraskeletal Ewing sarcoma in children, adolescents, and young adults. An analysis of three prospective studies of the Cooperative Weichteilsarkomstudiengruppe (CWS). Issue 10 (5th June 2021) - Koscielniak, Ewa; Sparber‐Sauer, Monika; Scheer, Monika; Vokuhl, Christian; Kazanowska, Bernarda; Ladenstein, Ruth; Niggli, Felix; Ljungman, Gustaf; Paulussen, Michael; Bielack, Stefan S.; Seitz, Guido; Fuchs, Joerg; et al.
Abstract: Background: We have analyzed the outcome of patients with localized extraskeletal Ewing sarcoma (EES) treated in three consecutive Cooperative Weichteilsarkomstudiengruppe (CWS) soft tissue sarcoma (STS) studies: CWS‐91, CWS‐96, and CWS‐2002P. Methods: Patients were treated in CWS‐91 with four‐ (vincristine, dactinomycin, doxorubicin, and ifosfamide [VAIA] or cyclophosphamide [VACA II]) or five‐drug (+etoposide [EVAIA]) cycles, in CWS‐96 they were randomly assigned to receive VAIA or CEVAIE (+carboplatin and etoposide), and in CWS‐2002P with VAIA III plus optional maintenance therapy (MT) with cyclophosphamide and vinblastine. Local therapy consisted of resection and/or radiotherapy (RT). Results: Two hundred forty‐three patients fulfilled the eligibility criteria. The 5‐year event‐free survival (EFS) and overall survival (OS) were 63% (95% confidence interval [CI] 57–69) and 73% (95% CI 67–79), respectively. The 5‐year EFS by study was 64% (95% CI 54–74) in CWS‐91, 57% (95% CI 48–66) in CWS‐96, and 79% (95% CI 67–91) in CWS‐2002P (n.s.). The 5‐year OS was 72% (95% CI 62–82) in CWS‐91, 70% (95% CI 61–79) in CWS‐96, and 86% (95% CI 76–96) in CWS‐2002P (n.s.). In CWS‐96, 5‐year EFS and OS in the VAIA arm versus the CEVAIE were 65% (95% CI 52–81) versus 55% (95% CI 39–76) log‐rank p = .13, and 85% (95% CI 75–96) versus 61% (95% CI 45–82), log‐rank p = .09. Conclusion: Our analysis provides interesting information on the treatment and specificities of EES, which can be useful for a better understanding of this rare entity and should be considered in the development of future clinical trials for Ewing sarcoma defined as FET–ETS fusion positive tumors.